Production of JeKo Candy (Jeli Kelor) as an Effort to Prevent Stunting in Lengkese Village, Takalar Regency - Fajriansyah, Fajriansyah; Zulfahmidah, Zulfahmidah; Nurkhairi, Nurkhairi (Fakultas Kedokteran Universitas Muslim Indonesia, 2023)
Moringa plant is one of the plants that can be found in Lengkese Village, District, Takalar Regency. There is a Takalar Regency government policy that requires every house to plant at least 1 moringa plant for 1 house so that this plant is easy to find in the yards of the houses of the Lengkese Village community. It is known that Moringa leaves are plants that have many benefits, one of which is as an alternative to improve the nutritional status of malnourished children, overcome malnutrition, and increase the amount of milk production in nursing mothers. Some of the obstacles faced by the people of Lengkese Village, Takalar Regency as our community service partners include: (1) Activities in the Lengkese Village community who have free time that has not been used for productive activities, (2) Processing, The community in Lengkese Village only uses Moringa leaves as hedges which are left attached to the terraces of the house. Through this community service program, we facilitate partners through counseling, training/assistance, and fostering the production of JeKo (Moringa Jelly) candy as an effort to prevent stunting (malnutrition). The specific target achieved from the application of community science and technology through this training is an increase in understanding, knowledge and skills of group partners, partners are able to produce packaged and labeled JeKo products equipped with partner identities.